Flat top solitons on linear gaussian potential - Umarov, Bakhram A.; Mohd Busul Aklan, Nor Amirah; Rosly, M.R.; Hassan, Torla (Institute of Physics (IOP), 2017)
The study of Nonlinear Schrodinger Equation has been wide focus from many researchers especially analysing the result of collision as it describes the soliton propagation. This paper considers the soliton scattering of cubic-quintic Nonlinear Schrodinger Equation on localized Gaussian potential. By applying Super-Gaussian ansatz as the trial function for variational approximation (VA) method, the soliton interaction may acquire flat-top shape with appropriate parameters. The result of VA will be compared to numerical analysis to check the accuracy of analytical predictions.